Letter (copy) : Basque Children's Trust Limited - Tewson, Vincent
1942-07-23 038-0025-001 Secretary's HVT/FC/KA/1744 RAP/MA 23rd July 1942 Mr. R.A. Palmer Co-operative Union Ltd. Holyoake House Hanover Street, Manchester 4 Dear Mr. Palmer, BASQUE CHILDREN'S TRUST LTD. Referring to your letter of the 16th instant, when the basque children originally came to this country the T.U.C and the Labour Party participated in the work of the Basque Children's Committee and granted sums of money out of our Spanish Relief Fund to assist in the maintenance of the children. We have not made any grants recently but you may take it that any grants made specifically for the Basque Children's Trust Ltd. would be quite in order. Originally there were two committees - the National Joint Committee for Spanish Relief and the National Committee for the Care of Basque Children. We were represented on the latter Committee, but when 292/946/38/25(I)